PERSPEKTIF PEMBUDIDAYA IKAN MUJAIR TERHADAP PEMELIHARAAN SISTEM RESIRKULASI RAMAH LINGKUNGAN - Raflen Aril Gerungan; Indra Fransiskus Xaverius Rompas; Mecky Christofel Telis Pandelaki (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2021)
Understanding the recirculation system as an environmentally friendly ecosystem-based fish farming method is the main thing that fish cultivators can apply in achieving sustainable fish farming. The objective of this research was to determine the perceptions of the fish cultivator community about the recirculation system. This research uses a quantitative approach with descriptive research methods. There are 21 respondents of which 19.05% with junior high school education and 80.95% senior high school. Respondents had more than 10 years as fish farmers. The results showed that the majority of respondents had a good perception of the recirculation system (57.10%) and the minority had a poor perception (42.90%). Furthermore, the perception of willingness to adopt a recirculation system, the majority of respondents did not have a willingness to adopt, 57.10% and a minority had a willingness to adopt 42.90%. In this study, it can be concluded that the understanding and knowledge of fish cultivators regarding the benefits and advantages of the recirculation system in fish farming will encourage good perceptions, on the other hand, if fish farmers have minimal understanding and knowledge, the majority of fish cultivators have doubts and a lack of willingness to adopt the recirculation system.